2012
DOI: 10.1186/1471-2407-12-251
|View full text |Cite
|
Sign up to set email alerts
|

Impact of partial versus whole breast radiation therapy on fatigue, perceived stress, quality of life and natural killer cell activity in women with breast cancer

Abstract: IntroductionThis pilot study used a prospective longitudinal design to compare the effect of adjuvant whole breast radiation therapy (WBRT) versus partial breast radiation therapy (PBRT) on fatigue, perceived stress, quality of life and natural killer cell activity (NKCA) in women receiving radiation after breast cancer surgery.MethodsWomen (N = 30) with early-stage breast cancer received either PBRT, Mammosite brachytherapy at dose of 34 Gy 10 fractions/5 days, (N = 15) or WBRT, 3-D conformal techniques at do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 77 publications
(101 reference statements)
3
31
0
3
Order By: Relevance
“…This may be attributed to physical and psychological exhaustion caused by cancer treatment and distressing side effects. Similar findings were reported by Albuquerque Kevin et al [6] in a prospective longitudinal study to examine the effect of radiation therapy on fatigue and it were reported that higher duration of radiation therapy was significantly associated with level of fatigue (p= 0.02).…”
Section: Discussionsupporting
confidence: 76%
“…This may be attributed to physical and psychological exhaustion caused by cancer treatment and distressing side effects. Similar findings were reported by Albuquerque Kevin et al [6] in a prospective longitudinal study to examine the effect of radiation therapy on fatigue and it were reported that higher duration of radiation therapy was significantly associated with level of fatigue (p= 0.02).…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, a shorter period of time needed to deliver treatment might improve the convenience and quality of life of the patients, possibly reducing the physical and psychological stress related to the radiotherapy [41,42]. For patients with several comorbidities, or for those who live far from radiation oncology centers, a short course of irradiation could increase their adherence and also reduce the likelihood of mastectomy [13,43].…”
Section: Discussionmentioning
confidence: 99%
“…Brachytherapy confers value to patients as total treatment time is decreased and radiation-related fatigue may be lessened (24), yet such gains could be offset by higher recurrence risks or much higher costs, either from brachytherapy itself or salvage treatment (such as for recurrent disease, though this outcome was not directly measured in our current study) (25). Prior literature has sought to estimate value using costs derived from Medicare reimbursement (25,26), but such approaches are dated given changes to brachytherapy reimbursement that occurred in 2009 (27) and further do not extend to younger patients with private insurance.…”
Section: Discussionmentioning
confidence: 99%